Influence Product Quality and Quality of Service to Customer Satisfaction ( Renter ) Photocopy Machine Brand Konica Minolta in Surabaya - Kurniawan Agung Laksono; Elok Damayanti; I Gede Arimbawa (LPPM NAROTAMA UNIVERSITY, Indonesia, 2019)
This type of research is quantitative research, a population of 324 people from the customer (renter) photocopy machine Konica Minolta and taken 76 people using the formula slovin sample. The research method multiple regression analysis using SPSS 21. From the test results concluded that the hypothesis 1 hypothesis can be accepted, because of the results of the t test independent variable consisted of Product Quality and Service Quality partially significant effect on the variable Customer Satisfaction. Hypothesis 2 in accordance with the basis for a decision in the f test it can be concluded also that the variable quality of product and service quality variables simultaneously influence customer satisfaction.